2011
DOI: 10.1021/la102613f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Single-Stranded DNA Adsorption onto Citrate-Stabilized Gold Nanoparticles in Colloidal Solution

Abstract: A variety of rapid biomolecular assays under development rely on the selective adsorption of single-stranded DNA onto unfunctionalized, negatively charged, citrate-stabilized gold nanoparticles. We investigate the adsorption mechanism with a study of the binding kinetics and find strong evidence for the dominance of hydrophobic effects including linear compensation between the activation energy and the natural log of the Arrhenius prefactor and the correlation of the adsorption rate in the presence of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 73 publications
6
144
0
1
Order By: Relevance
“…[29] The interaction between DNA and negatively charged metallic nanoparticles has been studied for many years. [13,30,31] It has been shown that the difference between the adsorption of a ssDNA and that of a dsDNA to metal nanoparticles leads to the protection of nanoparticles against salt-induced aggregation to different extents. In fact, the reasons for a rather complex interaction between ssDNA and GNPs include coordination between nitrogen atoms and GNPs and also the softness and random coil-like structure of ssDNA compared to the rigid structure of dsDNA, which gives ssDNA more freedom to wrap around GNPs and stabilise them.…”
Section: Interaction Of Aptameth and Gnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] The interaction between DNA and negatively charged metallic nanoparticles has been studied for many years. [13,30,31] It has been shown that the difference between the adsorption of a ssDNA and that of a dsDNA to metal nanoparticles leads to the protection of nanoparticles against salt-induced aggregation to different extents. In fact, the reasons for a rather complex interaction between ssDNA and GNPs include coordination between nitrogen atoms and GNPs and also the softness and random coil-like structure of ssDNA compared to the rigid structure of dsDNA, which gives ssDNA more freedom to wrap around GNPs and stabilise them.…”
Section: Interaction Of Aptameth and Gnpsmentioning
confidence: 99%
“…Apparently, this effect is the result of the complex interactions between DNA and GNPs, which include electrostatic and hydrophobic effects. [31] …”
Section: Interaction Of Aptameth and Gnpsmentioning
confidence: 99%
“…The only required reagent is a low pH citrate buffer. Most previous work on tuning the AuNP/DNA interaction employs only salt, 19,[23][24][25] while the effect of pH remains largely unexplored. 18,26 Our discovery reveals a new way to control DNA adsorption, which is quite different from using salt and is likely to find applications in many areas involving AuNPs and DNA.…”
mentioning
confidence: 99%
“…The interaction between nucleosides and AuNPs is quite complicated and has been the subject of extensive debate. Briefly, binding of nucleosides to AuNPs via nitrogen has been reported [35,36], and in other work hydrophobic interactions were indicated as the main mechanism of adsorption [37]. These differences in the interaction responsible for adsorption partially derive from different colloidal compositions of the adsorbate solution, the NP surface, and the media.…”
Section: Loading Of Conjugate Adenosines Onto Aunpsmentioning
confidence: 97%